The unknown epistolary heritage of professor Petar Dinekov in the Sofia Branch of the Central State Archives of Bulgaria: a contribution to our cultural history (Research Announcements "Heritage BG", 2025)
Prof. P. Dinekov is one of the most eminent Bulgarian humanities scholars of the twentieth century, who has his own place in Bulgarian science and Bulgarian culture. The discovery of a vast array of unprocessed Polish correspondence in his personal collection – 1987K – in the Central State Archives has become a kind of cultural event. These are letters addressed to P. Dinekov by Polish scholars and intellectuals from various humanitarian fields. The aim of my study is to reveal the intellectual processes that ranked our intellectuals next to the European ones in the recent past, namely from the 30s to the 90s of the 20th century. References:Belcheva 2016: Belcheva, Evelina. Samoten v svoeto vreme. Book 1, Sofia.Belcheva 2016: Belcheva, Evelina. Zlatorozhkata wrazka (Petar Dinekov – Vladimir Vasilev, dva portreta v retro ot natura), Sofia.Bilyarska 2011: Bilyarska, Vasilena. Rannite dnevnitsi i spomeni na akad. Petar Dinekov. Razhdaneto na ucheniya i choveka na peroto. - Izvestiya na darzhavnite archivi, No. 101, 231–278.Bilyarska, 2016: Bilyarska, Vasilena. Kirilometodievistikata v lichniya arhiv na akademik Petar Dinekov v TSDA. PhD Dissertation, defended at the Cyrillo-Methodian Research Centre at the Bulgarian Academy of Sciences.Dinekov 2020: Petar Dinekov. Zapiski ot ‘prehoda’. Book 1 (October 17, 1989 – October 17, 1990). Manuscript reading and selection: Evelina Belcheva. Sofia.Dinekov 2021: Petar Dinekov. Zapiski ot ‘prehoda’. Book 2 (October 22, 1990 – February 22, 1992). Presented by: Evelina Belcheva. Sofia.Diaries 2015: Petar Dinekov. Dnevnitsi 1933–1992. Т. I (1933–1937; 1958–1966). Sofia.Vaptsarova, Ilieva 2014: Vaptsarova, Gabriela, Darina Ilieva. Balgaro-polski kulturni i nauchni vrazki XIX–XX vek na bazata na dokumentalni iztochnitsi ot NA–BAN. – In: Polsha i polyatsite v novata balgarska istoriya (sredata na XIX – sredata na XX vek), Sofia, 10–19. http://clphchm.bas.bg/archiv_doc_info/Conf_BG-PL_21-22032014.pdf
Keywords: archival documents; correspondence